Behavioral factors associated with SARS‐CoV‐2 infection in Japan. Issue 5 (26th April 2022) - Arashiro, Takeshi; Arima, Yuzo; Muraoka, Hirokazu; Sato, Akihiro; Oba, Kunihiro; Uehara, Yuki; Arioka, Hiroko; Yanai, Hideki; Yanagisawa, Naoki; Nagura, Yoshito; Kato, Yasuyuki; Kato, Hideaki; et al.
Abstract: Background: The relative burden of COVID‐19 has been less severe in Japan. One reason for this may be the uniquely strict restrictions imposed upon bars/restaurants. To assess if this approach was appropriately targeting high‐risk individuals, we examined behavioral factors associated with SARS‐CoV‐2 infection in the community. Methods: This multicenter case–control study involved individuals receiving SARS‐CoV‐2 testing in June–August 2021. Behavioral exposures in the past 2 weeks were collected via questionnaire. SARS‐CoV‐2 PCR‐positive individuals were cases, while PCR‐negative individuals were controls. Results: The analysis included 778 individuals (266 [34.2%] positives; median age [interquartile range] 33 [27–43] years). Attending three or more social gatherings was associated with SARS‐CoV‐2 infection (adjusted odds ratio [aOR] 2.00 [95% CI 1.31–3.05]). Attending gatherings with alcohol (aOR 2.29 [1.53–3.42]), at bars/restaurants (aOR 1.55 [1.04–2.30]), outdoors/at parks (aOR 2.87 [1.01–8.13]), at night (aOR 2.07 [1.40–3.04]), five or more people (aOR 1.81 [1.00–3.30]), 2 hours or longer (aOR 1.76 [1.14–2.71]), not wearing a mask during gatherings (aOR 4.18 [2.29–7.64]), and cloth mask use (aOR 1.77 [1.11–2.83]) were associated with infection. Going to karaoke (aOR 2.53 [1.25–5.09]) and to a gym (aOR 1.87 [1.11–3.16]) were also associated with infection. Factors not associated with infection included visiting a cafe with others, ordering takeout, using food delivery services, eating out by oneself, and work/school/travel‐related exposures including teleworking. Conclusions: We identified multiple behavioral factors associated with SARS‐CoV‐2 infection, many of which were in line with the policy/risk communication implemented in Japan. Rapid assessment of risk factors can inform decision making.